A modernidade arquitetônica dos hotéis de Fortaleza : uma análise sobre o reuso - Soares, Thaís Silveira (2022)
In recent years the examples of hotel architecture produced in modernity in Fortaleza have been gradually degraded, through processes that encompass not only their abandonment and mischaracterization, but also their complete extinction. These losses are caused both by the pressures imposed by the real estate market, as well as by the lack of knowledge of their patrimonial value by the population and by the lack of interest of the Public Power in preserving them. Therefore, this study has as main objective to discuss the reuse as a strategy for the conservation of hotel architecture, focusing and analyzing the interventions in hotels that hold characteristics of architectural modernity in Fortaleza, between the 1950s and 1980s. To this end, the research addresses the historical conjuncture of the city’s urbanization, contextualizing the emergence of the first hotels and relating them to the urban dynamics verified throughout the 20th century and the development of tourism. Attention is drawn to characteristics that already announced certain intentions of modernity, since the eclectic hotels of the 1930s, seeking to understand how it manifested itself in its different architectural expressions. Then, questions about use and reuse in historical heritage, and also about conservation and restoration theories are revisited, as well as a discussion about the specifics of modern architecture and the application of the theories studied in relation to the most recent heritage. Finally, three cases regarding hotels that received reuse interventions in Fortaleza will be analyzed, seeking to evaluate them from the perspective of materiality and heritage, raising questions to understand if the intervention choices for these buildings would be adequate from the conservation and safeguarding point of view. In this way, the present work intends to constitute a contribution to the historiography of the architecture of moderni- ty in Fortaleza, through the bibliographic review, the documentation and inventory of each chosen building, and the analysis undertaken, in turn, intends to serve as a theoretical and practical basis for a proper understanding of the reuse interventions that have been carried out in Fortaleza, as well as to support future academic studies or conservation concepts in the architecture cultural heritage of modernity.